Effect of Chlorhexidine 2% versus Alcohol 70% on Catheter -Related Bloodstream Infections in Neonates: Randomized Control Trial - El-Farrash, Rania A.; Ashour, Marwa Mamdouh; Ahmed, Marwa Adel; Farid, Yasmin A. (International Journal of Child Health and Nutrition, 2026)
Background: Central venous catheters (CVCs) are essential for neonatal intensive care but are strongly associated with catheter-related bloodstream infections (CRBSI), which significantly increase morbidity, mortality, and hospital stay. The optimal antiseptic for neonatal skin disinfection remains debated, with chlorhexidine-alcohol solutions increasingly recommended but still under investigation for safety and efficacy. Objective: To compare the effectiveness of 2% chlorhexidine in 70% isopropyl alcohol versus 70% alcohol alone in reducing catheter-related bloodstream infections among neonates requiring CVCs. Methods: A prospective randomized controlled trial was conducted on 100 neonates admitted to the NICU at Ain Shams University Hospital. Participants were randomly assigned to two groups: Group A (alcohol-only antisepsis) and Group B (chlorhexidine-alcohol antisepsis). Data collected included patient demographics, catheter type and duration, infection rates, blood culture results, inflammatory markers, and clinical outcomes. Results: Group B (chlorhexidine-alcohol) demonstrated significantly lower rates of positive blood cultures (notably Klebsiella and E. coli) compared to Group A. The incidence of infection was highest in neonates with percutaneous central venous catheters (PCVCs) and umbilical venous catheters (UVCs), while peripherally inserted central catheters (PICCs) showed the lowest infection burden. Mean catheter duration was 9-11 days, with most infections occurring beyond the seventh day. Hemoglobin and hematocrit levels declined significantly over time in infected cases. Group B also required fewer escalations to second-line antibiotics. Conclusions: Using 2% chlorhexidine in 70% isopropyl alcohol significantly reduced catheter-related bloodstream infections (CRBSIs) in neonates, compared to 70% alcohol alone. Peripherally inserted central catheters (PICCs) exhibited the lowest infection rates, highlighting the importance of both antiseptic selection and catheter type in neonatal infection prevention protocols.